2023
DOI: 10.1186/s40942-023-00511-7
|View full text |Cite
|
Sign up to set email alerts
|

Application and accuracy of artificial intelligence-derived large language models in patients with age related macular degeneration

Lorenzo Ferro Desideri,
Janice Roth,
Martin Zinkernagel
et al.

Abstract: Introduction Age-related macular degeneration (AMD) affects millions of people globally, leading to a surge in online research of putative diagnoses, causing potential misinformation and anxiety in patients and their parents. This study explores the efficacy of artificial intelligence-derived large language models (LLMs) like in addressing AMD patients' questions. Methods ChatGPT 3.5 (2023), Bing AI (2023), and Google Bard (2023) were adopted as LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…When it comes to comparing different AI chatbots, current literature suggests better performance of ChatGPT than Google Bard/Gemini in triaging and diagnosing simulated ophthalmic patient complaints [ 14 ] or in providing an accurate and coherent surgical plan for glaucoma [ 15 ] and vitreoretinal [ 16 ] cases. Furthermore, ChatGPT-3.5 was found to be more accurate than Bing and Google Bard/Gemini in answering patients’ questions about age-related macular degeneration [ 2 ]. Moreover, in a study evaluating the performance of ChatGPT (versions 3.5 and 4) and Google Bard/Gemini in answering common inquiries regarding ocular symptoms, it was found that ChatGPT-4 outperformed ChatGPT-3.5 and Google Bard; however, all chatbots exhibited only moderate self-awareness capabilities and modest self-improving capabilities over time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to comparing different AI chatbots, current literature suggests better performance of ChatGPT than Google Bard/Gemini in triaging and diagnosing simulated ophthalmic patient complaints [ 14 ] or in providing an accurate and coherent surgical plan for glaucoma [ 15 ] and vitreoretinal [ 16 ] cases. Furthermore, ChatGPT-3.5 was found to be more accurate than Bing and Google Bard/Gemini in answering patients’ questions about age-related macular degeneration [ 2 ]. Moreover, in a study evaluating the performance of ChatGPT (versions 3.5 and 4) and Google Bard/Gemini in answering common inquiries regarding ocular symptoms, it was found that ChatGPT-4 outperformed ChatGPT-3.5 and Google Bard; however, all chatbots exhibited only moderate self-awareness capabilities and modest self-improving capabilities over time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being developed as conversational artificial intelligence (AI) systems, large language model (LLM)-based chatbots are currently the focus of intense interest in the field of medicine, particularly in ophthalmology. For example, Chat Generative Pre-trained Transformer (ChatGPT) (OpenAI, San Francisco, California, United States), released in late 2022, has already shown remarkable ability in providing general information and advice for glaucoma [ 1 ] and age-related macular degeneration patients [ 2 ], answering ophthalmology StatPearls questions [ 3 ], and even helping triage ophthalmic emergency cases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…ChatGPT capabilities have been investigated in question comprehending and providing relevant responses as well. A study revealed that ChatGPT delivers responses that are 80% accurate and comprehensive in addressing the 16 most frequently asked questions about AMD, providing valuable information that individuals with AMD would find beneficial [54]. Additionally, another recent study showed the ChatGPT's ability to handle ophthalmic discharge summaries and operative notes.…”
Section: Artificial Intelligence-enabled Large Language Models In Oph...mentioning
confidence: 99%